Writing Assistance Through Education and Training of Paper-Writing for Students of the Faculty of Islamic Economics and Business IAIN Palangka Raya - Hasty Kusuma, Triana; Sabatino Zamzami, Ahmad (Amala Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of implementing community service (PKM) in the form of socialization and training is to provide understanding to students of the Islamic Economics and Business Faculty IAIN Palangka Raya about the systematics of writing scientific papers, especially making good and correct papers that are useful for later. This activity is also to increase student motivation to carry out quality scientific writing activities. The method of implementing this Community Service (PKM) activity uses the lecture and discussion method. This activity is carried out in 3 stages, namely the preparation stage, the serving stage, and the reflection stage. In the first stage, the Team collects information about errors that are often found in writing papers, designs and formulates the format of the guidelines and makes guidelines for writing papers and then coordinates with related parties (Leadership Leaders and Colleagues). The second stage, the service, is that the team conducts socialization activities on paper-making guidelines and conducts paper-making training to students at the Islamic Economics and Business Faculty, IAIN Palangka Raya. Furthermore, in the third stage, the author carried out an evaluation of the socialization and training of making papers for students of the Islamic Economics and Business Faculty, IAIN Palangka Raya. The results of this activity indicate that the socialization and training activities went well and smoothly. This certainly fosters enthusiasm for the participants, seen by the good response from the participants to the implementation of the socialization and training, seen from the many participants who were enthusiastic in asking the resource persons during the activity.